Transcriptomic profiling reveals response mechanisms of Lactuca indica seedlings to seawater irrigation stress - Cao, Dingding; Xiang, Lirong; Li, Ziling; Wei, Neng; Wang, Qingfeng (Frontiers in Plant Science, 2025)
IntroductionThe increasing global soil salinization has accelerated research on seawater irrigation agriculture. Developing wild vegetables through seawater irrigation could establish foundational strategies for utilizing island vegetable germplasm resources.MethodsThis study investigated two distinct leaf-shaped individuals (S and Y) of wild Lactuca indica (L. indica) through hydroponic experiments with diluted seawater during seedling stage. Physiological and morphological assessments revealed that Y exhibited superior seawater tolerance compared to S. Tissue-specific -plant transcriptome analysis identified key metabolic pathways and regulatory genes in roots, stems, and leaves.ResultsDifferential gene expression analysis showed tissue-specific enrichment patterns: leaves predominantly enriched light-harvesting complex (LHC) genes in photosynthesis pathways; stems exhibited upregulation in cutin, suberin, and wax biosynthesis pathways; while roots showed activation of nitrogen metabolism pathways.DiscussionBased on the data from transcriptomics, we infered that the key salt-tolerant candidate genes include: (1) leaf-specific LHC genes enhancing photosynthetic efficiency; (2) stem-expressed wax biosynthesis gene aldehyde decarbonylase CER1, and cytochrome P450 family members fatty acid omega-hydroxylase CYP86A4S and cytochrome P450 family 77 subfamily A (CYP77A); and (3) root-specific nitrogen metabolism regulators (nitrate reductase (NR), nitrate/nitrite transporter 2 (NRT2), and nitrite reductase (NirA). This study provides the comprehensive tissue-specific transcriptome profile of wild L. indica under seawater irrigation, predicting crucial metabolic pathways and candidate genes that might enhance seawater tolerance. Our findings establish a valuable reference for salt tolerance research in wild vegetables and offer potential genetic targets for improving crop resilience in saline-affected ecosystems.